CORRELATION OF CLINICAL EXAMINATION ANDMRI FINDINGS WITH ARTHROSCOPIC EVALUATIONOF MENISCUS TEARS AND CRUCIATE LIGAMENT RUPTURES - Saad Iqbal; Sumaiya Khan; Raza Mehmood; Muhammad Sufyan; Muhammad Kazim Najjad; Aimen Najam (Baqai Journal of Health Sciences)
Objectives: This study aimed to evaluate the correlation between clinical examination and MRI findings with arthroscopy in diagnosing meniscal tears and cruciate ligament ruptures.